Are Greens Healthy for Banks' Balance Sheets? - Herwadkar, Snehal S .; Dhingra, Sambhavi; Goel, Sonali; Nair, Rahul A. (Economic and Political Weekly, 2025)
There is an urgent need to channel lending towards green sectors to address climate change. The relationship between green lending by banks and their asset quality and profitability is examined using a data set of 33 Indian banks from March 2015 to Decemb
Keywords: Balance Sheets; Banks; Greens Healthy; Indian Banks